2004
DOI: 10.1051/forest:2004076
|View full text |Cite
|
Sign up to set email alerts
|

Predispositions and symptoms of Agrilus borer attack in declining oak trees

Abstract: -This paper presents results of a semi-quantitative study on the role of Agrilus biguttatus F. in oak decline in Belgium. Larvae of this insect breed in living subcortical tissues of European oak. Several factors favouring attacks are discussed, among which the overall health condition and the local physical and biochemical status of the host tree. Larvae, feeding galleries, pupae, imago and D-shaped emergence-holes of A. biguttatus were observed exclusively in declining and recently dead oaks. Attacks start i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(67 citation statements)
references
References 18 publications
4
55
2
Order By: Relevance
“…Oaks with crown ratings of ''3'' and ''4'' and high densities of emergence holes (ratings of 2-3) are not expected to recover from A. auroguttatus injury, so the injury ratings recorded at ICA sites are anticipated to lead to higher levels of tree mortality in this region in the near future. Vansteenkiste et al (2004) found similar relationships between degree of injury from A. biguttatus and progressive crown thinning. These declining oaks in San Diego Co. represent potential hazards to human safety and structures and are not likely to be saved by remedial insecticidal options or cultural control methods.…”
Section: Injury On Oaks By a Auroguttatus And A Coxalissupporting
confidence: 74%
See 1 more Smart Citation
“…Oaks with crown ratings of ''3'' and ''4'' and high densities of emergence holes (ratings of 2-3) are not expected to recover from A. auroguttatus injury, so the injury ratings recorded at ICA sites are anticipated to lead to higher levels of tree mortality in this region in the near future. Vansteenkiste et al (2004) found similar relationships between degree of injury from A. biguttatus and progressive crown thinning. These declining oaks in San Diego Co. represent potential hazards to human safety and structures and are not likely to be saved by remedial insecticidal options or cultural control methods.…”
Section: Injury On Oaks By a Auroguttatus And A Coxalissupporting
confidence: 74%
“…Ratings for crown thinning were found to correlate with the level of Agrilus spp. injury, and can be a generalized response for the health of hardwood trees (Katovich et al, 2000;Vansteenkiste et al, 2004;. Furthermore, crown condition, bark staining, and emergence holes were the main predictors of oak health associated with A. auroguttatus infestation in California .…”
Section: Statistical Analysesmentioning
confidence: 97%
“…However, when beetle emergence has been monitored along the length of felled trees, the majority of emergence holes (approximately 85%) were below 7 m [53], reducing the chances of missing them in ground-based observations. Further examination of felled trees with bark cracks and stem bleeds confirms that symptomatic trees always have insect galleries, but do not always have emergence holes [21]. In addition, the sampling for bacterial isolations was conducted from the ground on standing trees, so galleries were present at a height where emergence holes would be clearly visible.…”
Section: Discussionmentioning
confidence: 99%
“…The health of host trees affects their ability to defend themselves against insect invaders with carbon reserves, limiting the extent of callusing responses, which would otherwise reduce larval survival [30,55]. The processes of callusing and, in addition, flooding of galleries have been described as defence mechanisms against A. biguttatus attack [21,[23][24][25], although they have been little studied in this system. Host resistance has been more thoroughly investigated for A. planipennis [56] where bark phenolic composition affects resistance [57].…”
Section: Discussionmentioning
confidence: 99%
“…These factors are recognised to facilitate the spread of forest diseases, with the main concern being tree pests [1,2]. In Germany, oak forests become frequently infested by populations of the splendour beetle Agrilus biguttatus (Fabricius, 1777) and cuttings of trees suffering damage caused by these beetles caused a significant amount of unplanned harvests in Germany over the recent years [3,4]. Forest owners and managers are anxious about these problems, and are tackling the issues through frequent monitoring of oak forest stands.…”
Section: Introductionmentioning
confidence: 99%